Effects of polymer network on electrically induced reflection band broadening of cholesteric liquid crystals. Issue 11 (1st March 2017) - Yu, Meina; Wang, Ling; Nemati, Hossein; Yang, Huai; Bunning, Timothy; Yang, Deng‐Ke
ABSTRACT: The reflection band of polymer stabilized cholesteric liquid crystals with negative dielectric anisotropy can be broadened by DC electric fields, which was ascribed to the pitch gradient caused by the motion of the structural chirality, that is, the polymer network. They systematically varied the mixture components, such as the photo‐initiator concentration, the monomer functionality, and the chiral dopant, to explore their influences on the reflection band broadening behavior. They learned how to control the polymer network morphology and ion density, which in turn determined the reflection bandwidth. By optimizing the mixture, they have greatly enhanced the broadening effect and achieved large bandwidth at low voltages. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2017, 55, 835–846 Abstract : In polymer stabilized cholesteric liquid crystals, the polymer network is dispersed in the liquid crystal and has a strong aligning effect on the liquid crystal. Ions are trapped on the surface of the polymer network. When an electric field is applied, the polymer network moves under electrostatic force. The motion of the polymer network changes the helical pitch of the liquid crystal, which results in a broadening of the reflection band of the liquid crystal. The morphology of the polymer network is varied and this research examines its effect on the broadening is investigated.